Instructional leadership, school-based management, and the quality of project-based IPAS learning in elementary schools (Diniyah: Jurnal Pendidikan Dasar, 2026)
Project-based IPAS learning in elementary schools requires instructional guidance and school-level management support to ensure meaningful implementation of Kurikulum Merdeka. This study analyzed the influence of principals’ instructional leadership and school-based management optimization on the quality of project-based IPAS learning. A quantitative explanatory survey was conducted with 120 upper-grade elementary school teachers from 15 public elementary schools in Wonosobo Regency, Indonesia. Data were collected using structured Likert-scale questionnaires and analyzed through path analysis. The findings showed that principals’ instructional leadership had a significant positive effect on project-based IPAS learning quality (β = 0.47, p < 0.01). School-based management optimization also had a significant positive effect (β = 0.38, p < 0.01). Simultaneously, both variables explained 61.3% of the variance in learning quality. These findings indicate that project-based IPAS learning is strengthened when pedagogical leadership is aligned with participatory school governance, resource management, and accountability. The study highlights the importance of integrating instructional supervision and school-based management to improve curriculum implementation in elementary education.   Keywords: elementary school; instructional leadership; IPAS learning; Kurikulum Merdeka; project-based learning; school-based management